Analisis Margin Pemasaran Cap Tikus di Desa Atep Kecamatan Langowan Selatan - Luly, Chocho Valentino Andrew; Sondakh, Mex Frans Lodwyk; Loho, Agnes Estephina (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2025)
This study aims to analyze the marketing margin of Captikus in Atep Village, Langowan Selatan District. The research was conducted from August to November 2023 using purposive sampling method for farmers (2 people per area were taken who were actively trying) and snowball sampling for collectors and retailers. Primary and secondary data were analyzed descriptively quantitatively to calculate marketing margins, price shares, and distribution channels. The results showed a marketing margin of IDR 10,159/liter for collecting traders with a price share of 24%, while the margin for retailers reached IDR 12,777/liter with a price share of 31%. The purchase price of Captikus from farmers by collectors is IDR 18,729/liter, then sold to retailers for IDR 28,800/liter, and finally marketed to consumers at IDR 41,666/liter. These findings indicate that the Captikus marketing chain in the study location has a significant margin structure, with higher profit distribution at the retailer level.